Effects of Kinesio Taping® in treatment of Cellulite: Randomized controlled blind trial. - Silva, Rodrigo Marcel Valentim da; Cavalcanti, Rafael Limeira; Rêgo, Ludmila Martins de França; Nunes, Patrícia Fonseca Leite; Meyer, Patrícia Froes (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Cellulite is caused by congestion of fluid in the interstitial space generating an edematous and fibrotic disorder. The Kinesio taping is a resource consisting of an elastic bandage, placed on the skin and represent a form of intervention in the treatment of lymphedema and help in the removal of accumulated fluid. Objective: The aim of this study was to investigate the effects of Kinesio Taping ® in patients with cellulite. Method: We analyzed 24 patients with cellulite in the gluteal region (grades I, II and III), selected conventionally in Natal / RN, Brazil. The volunteers were randomly divided into two subgroups of 12 individuals - a control group (CG) and a treatment group (GKT). Both the CG as the GKT were evaluated before and after the experiment, using a specific cellulite assessment protocol and photogrammetry. Only in GKT, four applications of the bandage were made once a week, in the gluteal region. Results: In the findings, there was a significant reduction of cellulite grade in the CG (p = 0.03) and GKT (p = 0.01). However, there were no changes in the other variables assessed by the protocol in the two groups. In photogrammetric analysis, there was a significant clinical improvement in GKT, in comparison between the initial and final evaluation. The treatment notes assigned by the photogrammetry evaluators were higher in GKT (p<0.01). Conclusion: It can be concluded that treatment with KT was able to significantly decrease the grade of cellulite, so that the variables evaluated by the protocol probably not influence this process.